Clinical observation and therapeutic evaluation of intravenous pump of recombinant human endostatin combined with TP regimen in treating patients with advanced ovarian cancer - Chi Zhang (KeAi Communications Co., Ltd., 2015)
Objectives: To observe the curative effects and adverse reactions of recombinant human (rh)-endostatin injection combined with a TP regimen for treating patients with advanced ovarian cancer. Methods: Fifty-four patients with pathologically confirmed ovarian cancer were randomly divided into a combined treatment (intravenous pump of rh-endostatin + TP regimen) group and a control (single chemotherapy) group, twenty-seven patients in each group. All patients were given a conventional CT examination. The level of vascular endothelial growth factor (VEGF), the size of tumor before treatment, after 2 cycles and after 4 cycles of treatment were determined for the comparison of curative effects and adverse reactions. Results: The effective rate was 37.0% (10/27) and disease control rate was 63.0% (17/27) in the combined treatment group after 2 cycles of treatment. The effective rate was 25.9% (7/27) and disease control rate was 63.0% (17/27) in the control group. The comparison between these two groups showed no significant differences (P > 0.05). The effective rate was 63.0% (17/27) and disease control rate was 92.6% (25/27) in the combined treatment group after 4 cycles of treatment. The effective rate was 29.6% (8/27) and disease control rate was 63.0% (17/27) in the control group. The effective rate and disease control rate between these two groups after 4 cycles of treatment showed significant differences (P < 0.05). The incidences of cardiovascular toxicity, myelosuppression, sore muscles and joints, alopecia and gastrointestinal reaction was not significantly different between two groups (P > 0.05). Conclusion: The pump delivery of rh-endostatin can down-regulate the expression of VEGF in ovarian cancer and has the better curative effect and slighter adverse reactions. Keywords: Ovarian cancer, Recombinant human endostatin, Intravenous pump, Vascular endothelial growth factor, Angiogenesis